THE ENCOURAGEMENT OF ERGO-ICONIC SERVICE VALUES TOWARD AGILE GOVERNMENT TO IMPROVE THE GOVERNMENT SERVICE PERFORMANCE - Andriyansah, Andriyansah; Rulinawaty, Rulinawaty; Zainudin, Arif (CosmoGov: Jurnal Ilmu Pemerintahan, 2022)
This research aims to prove that government services adopting an ergo-iconic service can improve their services, their existence to think, become entrepreneurial government, build, and create innovative ideas. This research used e-questionnaires distributed using snowball sampling technique. There were 202 respondents collected in a month, 20 days on February to March in 2020. The questionnaires distributed through online media could limit the respondents to give their answers. If they are under 20 years old or same as those who have graduated from college, it could be assumed that they often do transactions service provided by the government. Ergo-iconic service values proposed in this research was used as the independent variable. This is proven to contribute positively and encourage agile government improvement and acceptance of community values. In addition, ergo-iconic values are able to touch and provide comfortable functions that succeed in improving government service performance. The originality of indicators in this research is ergo-iconic service values developed from previous researches. The implication of this research results is that the model of ergo-iconic service values can create public service performance and realize agile governmentgb777